Preparation of Community-Based Merdeka Curriculum Teaching Modules for The Association of Raudlatul Athfal Teachers (IGRA) in Surakarta City - Khasan Ubaidillah; Tri Utami; Mila Faila Shofa; Hanik Fitriyatun; Nurul Afiyah; Salamah Az Zahra; Hilma Aziza (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The lack of training facilities regarding the implementation of the Merdeka Curriculum for Raudlatul Athfal (RA) teachers constitutes a significant obstacle in curriculum adoption. This community service program aims to develop community-based Merdeka Curriculum teaching modules for the Association of RA Teachers (IGRA) in Surakarta City. Employing a qualitative descriptive method with a Community Based Research (CBR) approach, the program actively involved 67 RA teachers from 33 institutions under IGRA Surakarta. Data were collected through interviews, Focus Group Discussions (FGD), observation, and pre-test/post-test assessments. The results demonstrate that the CBR approach effectively enhanced teacher competence, with overall understanding improving by 51%, particularly in teaching module components (from 20% to 90%). The program produced 67 teaching modules, 33 P5PPRA modules, and 33 sets of assessment instruments, with 80% of modules achieving